The influence of privacy perceptions on online shopping behavior - a comparison between millennials and baby boomers - Brüseke, Liana (Student Undergraduate Research E-journal!, 2016)
Privacy and security perceptions are growing topics in e-commerce. To develop a successful marketing strategy, it is crucial to know and address privacy concerns to prevent them from negatively influencing the online shopping behavior of customers. Perceived risk and trust are chosen to measure privacy perceptions. This study focuses on two generational cohorts, the millennials and baby boomers. The aim of the research is to investigate differences in privacy perceptions influencing their online shopping behavior. The research question is answered by analyzing data from German respondents.